2000
DOI: 10.1002/(sici)1097-0290(20000720)69:2<227::aid-bit12>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature ionic liquids as replacements for organic solvents in multiphase bioprocess operations

Abstract: Organic solvents are widely used in a range of multiphase bioprocess operations including the liquid-liquid extraction of antibiotics and two-phase biotransformation reactions. There are, however, considerable problems associated with the safe handling of these solvents which relate to their toxic and flammable nature. In this work we have shown for the first time that room-temperature ionic liquids, such as 1-butyl-3-methylimi- dazolium hexafluorophosphate, [bmim][PF(6)], can be successfully used in place of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 0 publications
1
142
0
1
Order By: Relevance
“…Organic solvent, ionic liquid, and polymer and nonionic surfactant were chosen because water-organic solvent two-phase system (Daugulis 2001;Straathof 2003), water-ionic liquid two-phase system (Cull et al 2000), aqueous two-phase system (Kumn 1980), and cloud point system (Wang et al 2004;Wang and Dai 2010) were often used in extractive microbial fermentation. Submerged cultivation of Monascus in the presence of different kinds of nonaqueous solvents (4 g/l) had been carried out.…”
Section: Screening Nonaqueous Solvents For Permeabilization Of Intracmentioning
confidence: 99%
“…Organic solvent, ionic liquid, and polymer and nonionic surfactant were chosen because water-organic solvent two-phase system (Daugulis 2001;Straathof 2003), water-ionic liquid two-phase system (Cull et al 2000), aqueous two-phase system (Kumn 1980), and cloud point system (Wang et al 2004;Wang and Dai 2010) were often used in extractive microbial fermentation. Submerged cultivation of Monascus in the presence of different kinds of nonaqueous solvents (4 g/l) had been carried out.…”
Section: Screening Nonaqueous Solvents For Permeabilization Of Intracmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] To give a sense of the scope for these solvents, it is worth mentioning that recent studies have shown that ambient-temperature ionic liquids can be used as media for a wide range of chemical reactions, including hydrodimerization, 28 hydrogenation, [29][30][31][32][33][34] dimerization, 35 polymerization, 36 alkylation, 37 FriedelCrafts reactions, [38][39][40][41] Heck coupling, 42,43 the DielsAlder reaction [44][45][46] and enzymatic catalysis of biotransformations. 47 As part of a programme aimed at understanding more about the nature of these ambient-temperature ionic liquids, and how they compare with conventional solvents, we have undertaken a study of their polarity using the solvatochromic dye Nile Red (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative the use of an ionic liquid may be considered. A very early example for such a reaction has been reported by Cull in 2000 [360]. The ionic liquid, however, has to be biocompatible; it must not be toxic to the yeast, and its biocompatibility strongly depends on the nature of the composing cation and anion.…”
Section: Whole-cell Biocatalysis In Ionic Liquids and Deep Eutectic Smentioning
confidence: 99%
“…For cations possessing alkyl substituents, the length of these alkyl chains seems crucial: the longer the alkyl chains, the lower is the tolerance of the microorganism to the ionic liquid [361][362][363][364]. This might be due to an insertion of the cation into the yeast's membrane followed by its disintegration or by an accumulation of toxic molecules inside the cells [360,363].…”
Section: Whole-cell Biocatalysis In Ionic Liquids and Deep Eutectic Smentioning
confidence: 99%
See 1 more Smart Citation